Compliance Analysis For The Use Of Covid-19 Personal Protective Equipment (PPE) Based On The Theory Of Planned Behavior On Health Workers - Mimiet Ismurdijahmitra; Sentot Imam Suprapto; Ratna Wardani (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: One way to prevent the spread of the Covid-19 virus to health workers is to adhere to the use of personal protective equipment. Increased compliance by health workers will increase awareness of the dangers of Covid-19 infection. Methods: Use a cross-sectional approach to design and conduct a descriptive analysis of the research. The population of all health workers at the Usada Buana Inpatient Main Clinic Surabaya, with a sample of 102, was determined by a proportional random sampling technique. Structural Model Analysis (SEM-PLS) with significance T Value > 1.64, with steps: designing a measurement model (outer model), designing a structural model (inner model), constructing a path diagram, converting a path diagram to a system of equations, estimating path coefficient, loading, and weight, evaluating the goodness of fit, and hypothesis testing. Results: The results showed that 48% of the excessive or low intentions of health workers in the use of COVID-19 PPE can very well be explained by attitudes (X1), subjective norms (X2), and perceptions of behavioral control (X3). In the meantime, 65.1% of the excessive or low adherence to COVID-19 PPE in medical examiners can be defined with the aid of the version used in this study (the model idea of deliberate conduct), and other variables outside this study version explain the rest (34.1%). Conclusion: Attitudes, subjective norms, and perceived behavioral controls can affect compliance with PPE use through intention mediation. Further studies are also endorsed to behavior research on the layout of instructional interventions based totally on the Theory of planned conduct in enhancing medical experts' compliance with adherence to PPE.